Growth and yield of fenugreek (Trigonella foenum-graecum L.) as influenced by irri- gation levels and weed management practices - S S Meena, S K Malhotra, R S Mehta, B S Patel, R K Singh (Journal of Spices and Aromatic Crops, 2010)
A field experiment on effect of irrigation levels and weed management practices on growthand yield of fenugreek (Trigonella foenum-graecum) was conducted at Sardarkrushinagar(Gujarat). The study indicated that irrigation at IW/CPE ratio 1.0 gave significantly higherplant height, dry matter accumulation plant-1, leaf area plant-1 and leaf area index at all thegrowth stages and seed, haulm and biological yields over IW/CPE ratios 0.8 and 0.6. Numberof branches, number of nodules and their dry weight plant-1 were also highest with irrigationat IW/CPE ratio 1.0. Days to 50% flowering and maturity significantly increased withincreasing levels of irrigation from IW/CPE ratio 0.6 to 1.0. Besides weed free treatment,higher plant height, dry matter accumulation plant-1, number of nodules and their weightplant-1, number of branches plant-1, days to 50% flowering and maturity were recorded withweed control by pre-emergence application of Pendimethalin @ 0.75 kg ha-1 + Inter-culturingat 40 days after sowing (DAS) and hand weeding at 20 and 40 DAS which were significantlysuperior over rest of treatments. Application of irrigation at IW/CPE ratio 1.0 along withweed control by pre-emergence application of Pendimethalin @ 0.75 kg ha-1 + Inter culturingat 40 DAS is beneficial for realising better growth and productivity of fenugreek.